Influence of some fungal species on aflatoxin production by toxigenic strain of Aspergilus parasiticus on natural substrate - VARMA, C.S. (Indian Phytopathology, 2002)
A total of 15 co-inhabiting mycoflora organisms were tested for their ability to affect aflatoxin production by A. parasiticus in natural substrate under lab. conditions. All of the fungi tested inhibited aflatoxin production and was highest (96%) with A. niger and Trichoderma viride, 80-90% with Deightoniella torulosa, Chaetomium globosum and Curvularia lunata [Cochliobolus lunatus], and